Increase The Immune System With Exercise - Ujang Rohman; Santika Rentika H; Sumardi; Achmad Nuryadi; Luqmanul Hakim; Yandika Fefrian R (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Some of the important factors to monitor during exercise are training load / exercise, recovery, and illness / injury. Training load includes training duration, frequency, and intensity. What is considered during recovery is resting heart rate, fatigue, appetite, and sleep quality. The frequency, type, cause, place / position of the body where the illness / injury occurs, and how long it takes for the illness / injury to occur are important things that should not be overlooked (Malm et al., 2019). By monitoring these things independently at home, it is hoped that sports can take place safely and increase immunity during this corona pandemic. In order to prepare for offline learning, SMPN 1 Perak Jombang needs a lot of references on how to improve the immune system through sports in the pandemic era in order to avoid Covid-19. Starting from knowledge about immunity, increasing immunity by improving nutrition, increasing immunity by exercising and other knowledge that can provide benefits for all.